Strategi Peningkatan Keterampilan Menulis Dalam Pembelajaran Bahasa Arab - Nazwa Awallul Rahma; Rizka Adillah Lesmana; Zuriatun Fitrah; Maulidatul Husna Khoinur; Sakholid Nasution (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
This journal explores strategies aimed at enhancing Arabic writing skills (kitabah). The study investigates diverse approaches, including practical exercises, technological integration, and differentiation methods. The research reveals that engaging students in relevant writing activities and leveraging digital resources significantly contributes to the development of their creativity and proficiency. Moreover, the implementation of differentiated approaches proves effective in catering to the diverse needs of students. This abstract emphasizes the importance of employing varied and contextual strategies for optimal outcomes in teaching Arabic writing skills.